Non-Invasive Detection of Tumors by Volatile Organic Compounds in Urine - Tomoaki Hara; Sikun Meng; Yasuko Arao; Yoshiko Saito; Kana Inoue; Aya Hasan Alshammari; Hideyuki Hatakeyama; Eric di Luccio; Andrea Vecchione; Takaaki Hirotsu; Hideshi Ishii (Biomedicines)
Cancer is one of the major causes of death, and as it becomes more malignant, it becomes an intractable disease that is difficult to cure completely. Therefore, early detection is important to increase the survival rate. For this reason, testing with blood biomarkers is currently common. However, in order to accurately diagnose early-stage cancer, new biomarkers and diagnostic methods that enable highly accurate diagnosis are needed. This review summarizes recent studies on cancer biomarker detection. In particular, we focus on the analysis of volatile organic compounds (VOCs) in urine and the development of diagnostic methods using olfactory receptors in living organisms. Urinary samples from cancer patients contain a wide variety of VOCs, and the identification of cancer specific compounds is underway. It has also been found that the olfactory sense of organisms can distinguish cancer-specific odors, which may be applicable to cancer diagnosis. We explore the possibility of novel cancer biomarker candidates and novel diagnostic methods.